Planning and Scheduling for Maritime Container Yards Supporting and Facilitating the Global Supply Network - Li, Wenkai; Wu, Yong; Goh, Mark (Springer International Publishing : Imprint: Springer, 2015)
Maximizing reader insights into the challenges facing maritime supply chains and container port logistics service providers in Asia, this book highlights their innovative responses to these challenges through real-world case studies. With a focus on mathematical modeling, simulation and heuristics approaches, this book provides academics, engineers, container terminal operators, students in logistics and supply chain management with the latest approaches that can be used to address the planning and scheduling problem in large container terminal yards. This book can be used on a self-contained basis as teaching cases in an undergraduate or specialist class setting, or on techniques applied to maritime container operations for port operations.